2015
DOI: 10.1111/jfbc.12142
|View full text |Cite
|
Sign up to set email alerts
|

R amalina Lichens and Their Major Metabolites as Possible Natural Antioxidant and Antimicrobial Agents

Abstract: Three lichen species of Ramalina (R. farinacea, R. fastigiata and R. fraxinea) were examined. Evernic, fumarprotocetraric, lecanoric, stictic and usnic acid levels were determined by high performance liquid chromatography‐diode array detection. Acetone, methanol and ethanol were used to examine the efficiencies of different solvent systems for the extraction of lichen acids. The total phenol contents in the extracts were determined by the Folin–Ciocalteu method. The antioxidant capacities were determined by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
0
15
0
1
Order By: Relevance
“…[51] Likewise, Tay et al reported a MIC value of 132 lg/mL on both microorganisms. [53] MIC values of the methanolic extracts of both Ramalina species obtained by Sahin et al [52] against several bacterial strains (E. coli and S.aureus) ranged from 64 to 512 lg/mL. Thus, the Algerian Ramalina active extracts studied here seem to be more active on the same tested organisms.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…[51] Likewise, Tay et al reported a MIC value of 132 lg/mL on both microorganisms. [53] MIC values of the methanolic extracts of both Ramalina species obtained by Sahin et al [52] against several bacterial strains (E. coli and S.aureus) ranged from 64 to 512 lg/mL. Thus, the Algerian Ramalina active extracts studied here seem to be more active on the same tested organisms.…”
Section: Discussionmentioning
confidence: 47%
“…For instance, Esimone et al reported the MIC values for the R. farinacea hexanic extract of 199.53 lg/mL and of 125.89 lg/mL on C. albicans and S. aureus, respectively. [53] MIC values of the methanolic extracts of both Ramalina species obtained by Sahin et al [52] against several bacterial strains (E. coli and S.aureus) ranged from 64 to 512 lg/mL. [53] MIC values of the methanolic extracts of both Ramalina species obtained by Sahin et al [52] against several bacterial strains (E. coli and S.aureus) ranged from 64 to 512 lg/mL.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have reported EA is biologically active and that it severely inhibits the growths of the pathogenic fungi Pythium ultimum and Phytophthora infestans [ 15 ]. Another study showed that EA extracted from Ramalina fastigiata has antioxidant capacity and an antimicrobial effect on E. coli [ 16 ]. Others reported EA inhibits the proliferations of U-87 human glioblastoma cells and HeLa cells (a cervical cancer cell line) [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the tested lichen species, the methanol extract of R. fastigiata showed the best antibacterial activity with inhibition against 6 out of 7 bacteria. Preceding studies (Cansaran et al, 2007;Şahin et al, 2015;Ristic et al, 2016) reported that acetone extract of R. fastigiata showed effect against E. coli and S. aureus. Here, the antibacterial activity of R. fastigiata against S. epidermidis, S. pyogenes, P. vulgaris, K. pneumonia, and E. cloacae was investigated for the first time.…”
Section: Resultsmentioning
confidence: 99%